2011
DOI: 10.1007/s12064-011-0143-y
|View full text |Cite
|
Sign up to set email alerts
|

Perception–action loops of multiple agents: informational aspects and the impact of coordination

Abstract: Embodied agents can be conceived as entities perceiving and acting upon an external environment. Probabilistic models of this perception-action loop have paved the way to the investigation of information-theoretic aspects of embodied cognition. This formalism allows (i) to identify information flows and their limits under various scenarios and constraints, and (ii) to use informational quantities in order to induce the self-organization of the agent's behaviour without any externally specified drives. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…characteristic of winning. One attempt at formalising this kind of principle is the "empowerment" framework which does so using the language of information theory (18)(19)(20). Our implementation probably has most in common with this strand of the literature.…”
Section: Significance Statementmentioning
confidence: 99%
“…characteristic of winning. One attempt at formalising this kind of principle is the "empowerment" framework which does so using the language of information theory (18)(19)(20). Our implementation probably has most in common with this strand of the literature.…”
Section: Significance Statementmentioning
confidence: 99%
“…As opposed to Capdepuy et al [21], we assume a round-based, sequential interaction of agents to foster a thorough analysis of their behaviour and to make the anticipation process less complex. We formalize this assumption by decomposing the loop into a sequence of atomic perception-action loops.…”
Section: Embracing Multiple Agents and Anticipationmentioning
confidence: 99%
“…In a 2007 paper, Capdepuy et al [20] examined how the sharing of information influences empowerment as a trigger for complex collective behaviour. Later [21], they used the notion of multiple-access channels to model simultaneous interaction and relate coordination to information-theoretic limits of control.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the workshop puts an emphasis on principles based on information flows through the perception-action loops of embodied systems-relating GSO to the notion that cognition and action emerge from interactions between brain, body, and environment while optimizing task-independent objective functions (Ay et al 2008;Polani et al 2007). The contributions to this special issue are grouped into three clusters corresponding to (i) guided self-organization in robotic systems (Martius and Herrmann 2011), (ii) information-theoretic studies of the sensorimotor loop Capdepuy et al 2011;Still and Precup 2011), and (iii) self-organization in information processing networks (Boedecker et al 2011;Greshenson 2011;Lizier et al 2011). Martius and Herrmann (2011) postulate that autonomous robots can generate exploratory behavior by selforganization of the sensorimotor loop, and show that the behavioral manifold determined in this way can be modified in a goal-dependent way without reducing the selfinduced activity of the robot.…”
mentioning
confidence: 99%
“…The proposed optimization principle suggests that exploration emerges as a directed behavior that optimizes information gain, rather than being modeled solely as behavior randomization. Capdepuy et al (2011) propose a formalism for studying embodied cognition among multiple agents that allows to (i) identify information flows and their limits under various scenarios and constraints, and (ii) use informational quantities in order to induce the self-organization of the agents behavior without any externally specified drives. The central question investigated in this article is the impact of coordination between agents, and it is shown that, under some conditions, self-organizing systems based on information-theoretic quantities have a tendency to spontaneously generate coordinated behavior.…”
mentioning
confidence: 99%